p53-Induced Apoptosis Occurs in the Absence of p14(ARF) in Malignant Pleural Mesothelioma - Hopkins-Donaldson, Sally (Neoplasia Press Inc., 2006)
Malignant pleural mesotheliomas (MPMs) are usually wild type for the p53 gene but contain homozygous deletions in the INK4A locus that encodes p14(ARF), an inhibitor of p53-MDM2 interaction. Previous findings suggest that lack of p14(ARF) expression and the presence of SV40 large T antigen (L-Tag) result in p53 inactivation in MPM. We did not detect SV40 L-Tag mRNA in either MPM cell lines or primary cultures, and treatment of p14(ARF)-deficient cells with cisplatin (CDDP) increased both total and phosphorylated p53 and enhanced p53 DNA-binding activity. On incubation with CDDP, levels of positively regulated p53 transcriptional targets p21(WAF), PIG3, MDM2, Bax, and PUMA increased in p14(ARF)-deficient cells, whereas negatively regulated survivin decreased. Significantly, p53-induced apoptosis was activated by CDDP in p14(ARF)-deficient cells, and treatment with p53-specific siRNA rendered them more CDDP-resistant. p53 was also activated by: 1) inhibition of MDM2 (using nutlin-3); 2) transient overexpression of p14(ARF); and 3) targeting of survivin using antisense oligonucleotides. However, it is noteworthy that only survivin downregulation sensitized cells to CDDP-induced apoptosis. These results suggest that p53 is functional in the absence of p14(ARF) in MPM and that targeting of the downstream apoptosis inhibitor survivin can sensitize to CDDP-induced apoptosis.